INTERFERON ALPHA 2 APPLICATION IN TREATMENT FOR ACUTE RESPIRATORY VIRAL INFECTIONS AMONG CHILDREN - V.A. Petrov; T.V. Tsopa; T.O. Medvedeva; A.A. Arova; S.N. Targonsky; S.V. Usova (Вопросы современной педиатрии, 2007)
The authors studied the clinical efficiency and safety of interferon alpha-2 (Reaferon-Es-Lipint) in oral dosing within complex therapy for acute respiratory viral infections. Dynamics of the main clinical and laboratory symptoms proves high efficiency of a medication and expediency of its use for the treatment of acute respiratory viral infections among children. Key words: children, acute respiratory viral infections, treatment, interferon alpha 2.